RESULTS OF THE TECHNICAL INSPECTION OF THE LOAD-BEARING STEEL STRUCTURES OF THE ROOF LANTERN OF THE BUILDING OF IVAN FRANKO NATIONAL UNIVERSITY OF LVIV - Hnatiuk , О.; Osadchuk , Т.; Volynets , М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
A visual and instrumental inspection of the steel load-bearing structures of the roof lantern above the assembly hall was conducted to ascertain the geometric dimensions, identify main defects, and perform verification calculations of the bearing capacity due to the replacement of decorative glass following major repairs. The measurement plans and technical documentation about the replacement of the decorative glass were subjected to analysis, as were the technical conclusions derived from the inspection of the load-bearing steel structures and glazing of the roof lantern. The inspection revealed that the drainage system from the covering above the lantern and the integrity of the lantern's glazing had been restored after major repairs and were secure at the time of the inspection. No evidence of mechanical or corrosion damage to the glass and metal structures was identified. The protective paint layer and sealant remain intact. A verification calculation of the longest element of the metal glazing frame was performed. To achieve this, a fragment of the steel frame was calculated in the SCAD Office, taking into account the load from its weight and the weight of the glazing (which increased by 67 %). The weight of the glass in each cell was divided into three nodes for triangular elements and into four nodes for quadrangular elements. A verification calculation of the frame contour element of the light-transmitting part of the lantern in the plane of the floor was also carried out. The results of the calculation demonstrated that the maximum forces in the steel elements of the roof lantern exceed the design loads, indicating that their bearing capacity is adequate. To maintain the lantern, roof walkways were designed in the form of beams made of two wooden bars with a cross-section of 100×150 mm, which are recommended to be arranged along the lower belts of metal roof trusses.